Study protocol of a randomised controlled trial of prostate radiotherapy in high-risk and node-positive disease comparing moderate and extreme hypofractionation (PRIME TRIAL). Issue 2 (28th February 2020) - Murthy, Vedang; Mallick, Indranil; Gavarraju, Abhilash; Sinha, Shwetabh; Krishnatry, Rahul; Telkhade, Tejshri; Moses, Arunsingh; Kannan, Sadhna; Prakash, Gagan; Pal, Mahendra; Menon, Santosh; Popat, Palak; et al.
Abstract : Introduction: There has been an interest in studying the efficacy of extreme hypofractionation in low and intermediate risk prostate cancer utilising the low alpha/beta ratio of prostate. Its role in high-risk and node-positive prostate cancer, however, is unknown. We hypothesise that a five-fraction schedule of extreme hypofractionation will be non-inferior to a moderately hypofractionated regimen over 5 weeks in efficacy and will have acceptable toxicity and quality of life while reducing the cost implications during treatment. Methods and analysis: This is an ongoing, non-inferiority, multicentre, randomised trial (NCT03561961 ) of two schedules for National Cancer Control Network high-risk and/or node-positive non-metastatic carcinoma of the prostate. The standard arm will be a schedule of 68 Gy/25# over 5 weeks while the test arm will be extremely hypofractionated radiotherapy with stereotactic body radiation therapy to 36.25 Gy/5# (7 to 10 days). The block randomisation will be stratified by nodal status (N0/N+), hormonal therapy (luteinizing hormone-releasing hormone therapy/orchiectomy) and centre. All patients will receive daily image-guided radiotherapy. The primary end point is 4-year biochemical failure free survival (BFFS). The power calculations assume 4-year BFFS of 80% in the moderate hypofractionation arm. With a 5% one-sided significance and 80% power, a total of 434 patients will be randomised to both arms equally (217 in each arm). The secondary end points include overall survival, prostate cancer specific survival, acute and late toxicities, quality of life and out-of-pocket expenditure. Discussion: The trial aims to establish a therapeutically efficacious and cost-efficient modality for high-risk and node-positive prostate cancer with an acceptable toxicity profile. Presently, this is the only trial evaluating and answering such a question in this cohort. Ethics and dissemination: The trial has been approved by IEC-III of Tata Memorial Centre, Mumbai. Trial registration number: Registered with CTRI/2018/05/014054 (http://ctri.nic.in ) on 24 May 2018